Why was the era of Al-Ma’mun calling the golden age? لما ذا سميت عصر المأمون بعصر الذهبي؟ - Bano, Dr. Saeeda; Bano, Dr. Najma (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
Golden ages may have slightly different meanings; they could mean a period of successful conquest, or perhaps a period of peace. The Golden Age of Islam refers to the time when the Islamic empire and the religion of Islam grew rapidly both in terms of expanding land and cultural progress. It saw a massive expansion in the fields of science, medicine, engineering, education and the arts, which would form lasting influences on every part of our modern societies. The Islamic Golden Age closely coincided with the rise and fall of the Islamic Abbasid Caliphate (750-1258). In 762, reigning caliph Al-Mansur relocated the Abbasid capital from Damascus to Baghdad, effectively relocating the center of the Islamic world. Around that same time, the famous House of Wisdom, or Grand Library of Baghdad, was erected within the city. Hosting thousands of tomes, scrolls, ancient texts, and enterprising scholars from around the world, Baghdad’s House of Wisdom was the beating heart of the Islamic Golden Age. progress. https://doi.org/10.5281/zenodo.10519551